New management technology for arabica coffee: the cyclic pruning program for Arabica coffee - Verdin Filho, Abraão Carlos Verdin Filho Carlos; Volpi, Paulo Sérgio Volpi Sérgio; Gava Ferrao, Maria Amélia Gava Ferrão Amélia; Ferrão, Romário Gava Ferrão Gava; Mauri, Aldo Luiz Mauri Luiz; Fonseca, Aymbiré Francisco Almeida da Fonseca Francisco Almeida; Tristão, Fabiano Alixsandro Tristão Alixsandro; Andrade, Saul de Andrade Júnior Júnior (Coffee Science - ISSN 1984-3909, 2017)
This study aimed to better understand the productive behavior of Coffea arabica when cultivated using the new management of Cyclic Pruning Program for Arabica Coffee (CPPAC), stablished using the same principles of the Cyclic Pruning Program for Conilon Coffee. The experiment was carried out in Baixo Guandú, Espírito Santo state, in the Southeast region of Brazil, in order to test the conditioning of this new pruning management for Arabica coffee (CPPAC) over the crop yield of a plantation of Catuaí Vermelho IAC 81. It was found increased crop yield with use of the (CPPAC) over the traditional management of Arabica coffee, considering five consecutive years of production. The (CPPAC) technique can be used as a viable alternative for pruning management of Arabica coffee.